A GENDER-BASED ANALYSIS OF OBSERVANCE AND NON-OBSERVANCE OF CONVERSATIONAL MAXIMS IN FRONT OFFICE STAFF’S SPEECH AT RESTAURANTS IN UBUD DISTRICT - Ni Made Ayu Purnami; Pande Agus Adiwijaya (Getsempena English Education Journal, 2021)
This study was intended to investigate, describe and explain how conversational maxims are observed by the Front Office staff at restaurants in Ubud when they handle table reservation and what types of non-observance are committed by the Front Office staff in observing conversational maxims. The subjects were the Front Office staff at restaurants in Ubud district. The data for this naturalistic qualitative study were collected through observation and audio-recording which were then analyzed by using Paul Grice’s (1975) Cooperative Principle theory. In this research, there were 30 conversations of taking table reservation via telephone which were conducted by the front office staff at restaurants in Ubud sub-district when they handle table reservation. Generally, both male and female front office staff produced more observance of maxims than non-observance of maxims. The highest frequency of observance and non-observance of Gricean maxims produced by male front office staff was maxim of quantity (100%), then followed by flouting of maxims (62.5%), and infringing maxims (25%). The highest frequency of observance and non-observance of Gricean maxims produced by female front office staff was maxim of quantity (100%), then followed by flouting of maxims (68.1%), and infringing of maxims (9.0%). Moreover, there was no opting out of maxims and suspending of maxims occurred in the conversation. The utterances were obtained from 30 data in restaurant setting. In general, both male and female front office staff produced more observance of maxims than non-observance of maxims.